Small firms, R&D, technology and innovation in the UK a literature review - Hoffman, Kurt; Parejo, Milady; Bessant, John.; Perren, Lew.
This work offers a guide to the literature on small and medium-sized enterprises (SMEs) and their innovative activities. Gaps and deficiencies in the literature are indicated, as are areas for future research.
The importance of small and medium-sized enterprises (SMEs) in economic growth has made them a central element in much recent policymaking. Of particular interest have been policies designed to promote and facilitate the operation of the innovation process within SMEs, and there has been substantial expansion of this kind of effort. Despite this interest, the knowledge base about how SMEs actually undertake innovative activities remains limited. This paper reports on a literature survey of UK work over the past decade and tries to characterise the state of knowledge about SMEs and innovation. It concludes with a discussion of gaps and weaknesses in the literature and some requirements for future research in this field.